Analisa Pengujian Lelah Material Stainless Steel 304 Dengan Menggunakan Rotary Bending Fatigue Machine - Muharnif M; Randy Septiawan (Rekayasa Material, Manufaktur dan Energi, 2018)
Rotary Bending Fatigue is a test tool to determine the limits of fatigue that occur in material, where fatigue occurs due to loading. Fracture occurs because when the material has undergone a stress cycle that produces permanent damage as a process of changing the permanent structure at one point crack (crack) is done by varying loading, namely: 10kg load produces a voltage of 34.226 Mpa, Cycle 125321 within 123, 37 minutes . At 15kg load produces a voltage of 51.333 Mpa, Cycle110597 in 125.54 minutes. At 20kg load produces a voltage of 68.452 Mpa, Cycle 54527 in 32.37 minutes. At 25kg load produces a voltage of 85.565 Mpa, Cycle 28638 in time of 22.01. At 30kg load produces a 102.6786 Mpa Voltage, 19711 Cycle in 17.57 minutes. With the following conclusions, fatigue resistance in 304 Stainless Steel decreases with increasing voltage given.